Microemulsion-Based Polymer Gels with Ketoprofen and Menthol: Physicochemical Properties and Drug Release Studies - Filip Otto; Anna Froelich (Gels, 2024)
Ketoprofen is a non-steroidal, anti-inflammatory drug frequently incorporated in topical dosage forms which are an interesting alternatives for oral formulations. However, due to the physiological barrier function of skin, topical formulations may require some approaches to improve drug permeation across the skin. In this study, ketoprofen-loaded microemulsion-based gels with the addition of menthol, commonly known for absorption-enhancing activity in dermal products, were investigated. The main objective of this study was to analyze the physicochemical properties of the obtained gels in terms of topical application and to investigate the correlation between the gel composition and its mechanical properties and the drug release process. Microemulsion composition was selected with the use of a pseudoternary plot and the selected systems were tested for electrical conductivity, viscosity, pH, and particle diameter. The polymer gels obtained with Carbopol® EZ-3 were subjected to rheological and textural studies, as well as the drug release experiment. The obtained results indicate that the presence of ketoprofen slightly decreased yield stress values. A stronger effect was exerted by menthol presence, even though it was independent of menthol concentration. A similar tendency was seen for hardness and adhesiveness, as tested in texture profile analysis. Sample cohesiveness and the drug release rate were independent of the gel composition.